Scatter-plot analysis of microcracks pattern behaviour of weathered limestone at Batu Caves, Malaysia - Aminuddin N.J.; Pauzi N.I.M. (2023)
Scatter-plot analysis is used to determine the behavior of microcrack pattern of weathered limestone. The objective of this study is to identify the range sizes of grain size, microcrack length and micropores diameter as to know the parameters that affect the behavior of microcrack pattern using scatter-plot analysis. To conduct this research, the samples of various grade of weathered limestone are collected from Batu Caves area. Laboratory testing conducted for this research using Scanning Electron Microscope (SEM) image. Results from this studies revealed that the ranges for grade II to III for grain size is between 20 and 150 ?m, microcrack length is between 80 and 600 ?m and micropores diameter is between 40 and 325 ?m. Furthermore the results indicated that the ranges for grade IV to VI for grain size is between 25 and 250 ?m, microcrack length is between 100 and 8000 ?m and micropores diameter is between 60 and 380 ?m. The results confirmed that grain size, microcrack length and micropores are important parameters in the assessment of the behavior of microcrack pattern of weathered limestone.